The Roles Of Taiwan Government Policy And Research Institutes In Promoting Innovation Practices In Electronics Industry: A Case Study - Soon, Eng Leong (2012)
Taiwan government intervention through National Innovation System (NIS) policy and research institutes, produced success local electronics industry with many components manufacturing, OEM and Information Technology products makers to support global markets. High speed of globalization triggers continual electronics products supply and demand competition, which might cause Taiwan electronics industry losing its competitive advantages to others emerging countries like Korea, Singapore and Malaysia.